Monetary policy, macroprudential policy and financial stability - Laeven, Luc,Maddaloni, Angela,Mendicino, Caterina (European Central Bank, 2022)
Recent research developed under the ECB research task force on Monetary Policy, Macroprudential Policy and Financial Stability highlights the existence of trade-offs and spillovers that monetary policy and macroprudential authorities face when deciding on their policy interventions, Monetary policy measures are key to support the supply of credit to the economy, but they could also have unintended consequences on financial stability risks. Macroprudential policies are instead effective in limiting financial stability risks, but they could also reduce the length of economic expansions by preventing credit from flowing to productive economic activities, In addition, since monetary and macroprudential policies transmit to the broad economy via the financial system, they unavoidably affect each other's effectiveness, Taking these factors into account is key for the design and implementation of both policies.
10.2866/919182
Keywords: Graue Literatur; risk taking; financial frictions; systemic risk; policy trade-offs